2014
DOI: 10.1016/j.canlet.2014.03.001
|View full text |Cite
|
Sign up to set email alerts
|

PI3K/mTOR dual inhibitor NVP-BEZ235 decreases Mcl-1 expression and sensitizes ovarian carcinoma cells to Bcl-xL-targeting strategies, provided that Bim expression is induced

Abstract: We previously showed that Bcl-xL and Mcl-1 cooperatively protect platinum-resistant ovarian cancer cells from apoptosis. Here we assessed the anticancer potential of combining ABT-737-induced inhibition of Bcl-xL with Mcl-1 inhibition via PI3K/Akt/mTOR pathway disruption using NVP-BEZ235. NVP-BEZ235 inhibited cell proliferation without inducing apoptosis. It strongly repressed Mcl-1 expression and induced Puma expression in both cell lines tested while differentially modulating Bim between the two. Interesting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
45
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(55 citation statements)
references
References 52 publications
8
45
2
Order By: Relevance
“…In ovarian cancers, we previously showed that Bcl-x L and Mcl-1 antiapoptotic proteins cooperate to protect resistant cells from apoptosis as their concomitant inhibition results in massive apoptotic cell death (5-7). Moreover, there is growing evidence to suggest that their BH3-only proapoptotic partner Bim is a crucial actor in induced cell death (8)(9)(10). These observations open up several therapeutic opportunities as they suggest that ovarian cancer cell apoptosis can be triggered by inhibiting Bcl-x L and Mcl-1 and/or by promoting their BH3-only partners, especially Bim.…”
Section: Introductionmentioning
confidence: 99%
“…In ovarian cancers, we previously showed that Bcl-x L and Mcl-1 antiapoptotic proteins cooperate to protect resistant cells from apoptosis as their concomitant inhibition results in massive apoptotic cell death (5-7). Moreover, there is growing evidence to suggest that their BH3-only proapoptotic partner Bim is a crucial actor in induced cell death (8)(9)(10). These observations open up several therapeutic opportunities as they suggest that ovarian cancer cell apoptosis can be triggered by inhibiting Bcl-x L and Mcl-1 and/or by promoting their BH3-only partners, especially Bim.…”
Section: Introductionmentioning
confidence: 99%
“…MtBIO can influence metabolic remodeling of cancer cells through a number of ways, such as, production of different metabolites, generation of reactive oxygen species (ROS), stabilization of hypoxia [31,32]. Taken together, it can be considered that there is a strong relationship between chemoresistance and MtBIO in ovarian cancer.…”
Section: Mtbio and Metabolismmentioning
confidence: 99%
“…MtBIO is the production of daughter mitochondria usually from previously existed one through a division process of called fission, subsequent growth, and maintenance by fusion and autophagy of mitochondria (mitophagy) [24]. Currently it has been observed that MtBIO is associated with cancer chemoresistance [25,26] through the modulation of associated proteins such as methylation-controlled J-protein (MCJ, also known as DNAJC15) [25,27], prohibitin 1 (PHB-1) [28][29][30], myeloid cell leukemia sequence 1 (MCL-1) [31,32] etc. in ovarian cancer.…”
Section: Introductionmentioning
confidence: 99%
“…BEZ235 is a potent PI3K/mTOR dual inhibitor that blocks both class I PI3K and mTOR1/2 through competition for the ATP-binding sites of these enzymes . In vitro and in vivo studies have shown its high anti-proliferative activities in neoplastic cells as well as a reduction in the phosphorylation level of AKT and its downstream proteins (Jebahi et al, 2014;Maira et al, 2008;Serra et al, 2008). BEZ235 is currently in phase 1/2 clinical trials and is being tested against a number of solid tumours including breast, endometrial, renal and pancreatic tumours.…”
Section: Accepted Manuscriptmentioning
confidence: 99%